PALEOSTRESS ANALYSIS TO INTERPRET THE LANDSLIDE MECHANISM: A CASE STUDY IN PARANGTRITIS, YOGYAKARTA - Salahuddin Husein; Ignatius Sudarno; Subagyo Pramumijoyo; Dwikorita Karnawati (Journal of Applied Geology, 2015)
Paleostress analysis on the landslide boundary faults is able to explain the sliding mechanism. This method is particularly useful to study a paleolandslide. About 30 striated fault planes from the Parangtritis paleo-landslide, located in the Yogyakarta coastline, were analyzed to define their principle stress axes. The eastern boundary fault, named as the Girijati Fault, was the main fault responsible for the mass movement and leaving a considerable steep cliff. It moved normal in a left lateral sense with ENE – WSW extension and dragged the rockmass southward, creating a NNW – SSW extension along the Parangtritis Fault and turn it into the western boundary fault. The rockmass slided along the stratigraphic contact between the underlying Nglanggran Formation and the overlying Wonosari Formation, created a semi-circular crown cliff as the northern boundary and produced some isolated topographic highs of the thrust block near the toe. Keywords: Paleostress, landslide boundary, fault, paleolandslide